Perceptions of the Ethical Work Climate and Covenantal Relationships - Barnett, Tim (Journal of business ethics, 2002)
Employees’ perception of the existence of a covenantal relationship between themselves and their employer indicates that they believe there is a mutual commitment to shared values and the welfare of the other party in the relationship. Research suggests that these types of employment relationships have positive benefits for both employees and employers. There has been little research, however, on the factors that determine whether such relationships will develop and thrive., In this paper, we suggest that the organization’s ethical work climate may be an important factor affecting employees’ perceptions about the nature of the relational contract between themselves and their employer. Specifically, we argue that work climates emphasizing benevolence and principle will be associated with covenantal relationships. Conversely, we believe that work climates emphasizing egoism will make it less likely that covenantal relationships will develop between an employer and employee., In order to test our hypotheses, we collected data from 194 employees of a large retail department store. The employees perceived their work climates in terms of principle (laws and professional codes) and benevolence, but to a lesser extent also believed that egoism (self interest) concerns characterized their climate. After controlling for demographic and job-related variables, we found (as expected) that measures of principled and benevolence climate were positively associated with covenantal relationships and that a measure of egoistic climate was negatively associated with covenantal relationships. In the final section of the paper, we discuss the implications of these findings for research and practice.